The Prevalence and Intensity of Neobenedenia girellae in Barramundi (Lates calcarifer) in Lampung and Situbondo Waters - Muhammad Aiman Yudarana, ,- (SIKIA Unair Banyuwangi, 2022)
Barramundi (Lates calcarifer) is a fish that has high economic value and has the potential to be developed in Indonesia. One of the species reported to barramundi is infest Neobenedenia girellae. This study aims to determine the prevalence and intensity of the parasitic worm Neobenedenia girellae in barramundi in the waters of Lampung and Situbondo. Sampling of barramundi with a size of 21 - 30 cm as many as 40 fish from Lampung waters and 50 barramundi from Situbondo waters. The results showed that there was worm infestation Neobenedenia girellae on barramundi in the waters of Lampung and Situbondo. The prevalence value of Neobenedenia girellae in barramundi in Lampung waters is 92% with almost always category and intensity value of 1.37 with low category when in Situbondo waters the prevalence value is 92% with almost always category and the intensity value is 1.67 with low category.